Clinical signs synovial fluid cytology and growth factor concentrations after intra-articular use of a platelet-rich product in horses with osteoarthritis - Goddard, Amelia (University of Pretoria, 2018)
Dissertation (MMedVet)--University of Pretoria, 2017.